Obesity and Severity COVID-19 : Literature Review Study - Disa Hijratul Muharramah; Nurhayati Prihartono (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2021)
Background: Coronavirus disease (COVID-19) caused by SARS-CoV 2 (Severe Acute Respiratory Syndrome) has spread worldwide and infected more than 180 million confirmed cases and 3,9 million deaths. The clinical manifestations of COVID-19 range from asymptomatic or mild infection to severe. Previous reports identified that obesity is associated with the condition of a person infected with COVID-19 develop into severe. This study aims at examining the risk of severity COVID-19 associated with obesity Methods: This study was conducted a literature review method. There are ten articles obtained from online databases at Pubmed, Google Schoolar and the Wiley Online Library.Result: The results of various studies using cohort and cross-sectional study designs show that obesity has a statistically significant association with increasing risk for the severity of COVID-19. Obese individuals infected with COVID-19 suffer severe and critical symptoms that impact patients admitted to ICU, intubation and death.Conclusion : Obesity increase the risk for severity of COVID-19. Maintain healthy life style, including routine exercise, choice of healthy food and routine medical checkup may reduce the risk of severity of COVID-19